Founding Environment, Inward Internationalization, and Firm Performance: Evidence from Chinese Private Enterprises. Issue 4 (1st October 2016) - Zhao, Hongxin (John); Ma, Jieqiong (Jeccy)
ABSTRACT: The Chinese economic transition from a centrally planned economy to a free market economy since 1978 has witnessed local private enterprises as underdogs . Compared with state-owned enterprises that benefit from soft budget constraints, private enterprises in China suffer from two institutionally induced pressures: legitimacy-lacking and resource-constraining pressures. Extending the insights from organizational imprinting theory, this article argues that the pressures from the past motivate Chinese private enterprises to seek legitimacy and knowledge through inward internationalization, and that inward internationalization would help private enterprises to achieve better performance. On the basis of 2, 565 private enterprises in China, we find that the adverse founding environment prompt private firms to undertake a high degree of inward internationalization, which further enhances their subsequent performance. We also find that this performance-enhancing effect becomes stronger in regions with more developed intermediate institutions and high foreign direct investment density.